Cisco PIX firewalls : configure, manage, & troubleshoot - Behrens, Thorsten; Riley, Charles; Khan, Umer (Syngress Pub., 2005)
Umer Khan's first book, "Cisco Security Specialist's Guide to PIX Firewalls," ISBN: 1931836639, has consistently maintained its spot as the #1 best-selling PIX book on amazon.com by providing readers with a clear, comprehensive, and independent introduction to PIX Firewall configuration. With the market for PIX Firewalls maintaining double digit growth and several major enhancements to both the PIX Firewall and VPN Client product lines, this book will have enormous appeal with the audience already familiar with his first book. * The Cisco Pix firewall is the #1 market leading firewall, owning 43% market share. Cisco is poised to release the newest, completely re-designed version 7 of the Pix operating system in the first quarter of 2004. * "Cisco Pix Firewalls: configure, manage, troubleshoot" Covers all objectives on the new Cisco Pix certification exam, making this book the perfect study guide in addition to professional reference. * Umer Khan's first book "Cisco Security Specialist's Guide to PIX Firewall" has been the #1 market leading Cisco Pix book since it was published in 2002